2013
DOI: 10.1155/2013/246797
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Dryness as a Measure of a Specific Spiritual Crisis in Catholic Priests: Associations with Symptoms of Burnout and Distress

Abstract: Spirituality/religiosity is recognized as a resource to cope with burdening life events and chronic illness. However, less is known about the consequences of the lack of positive spiritual feelings. Spiritual dryness in clergy has been described as spiritual lethargy, a lack of vibrant spiritual encounter with God, and an absence of spiritual resources, such as spiritual renewal practices. To operationalize experiences of “spiritual dryness” in terms of a specific spiritual crisis, we have developed the “spiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 31 publications
4
63
1
5
Order By: Relevance
“…Likewise, experiential representations of God or "heart knowledge" (Zahl and Gibson 2012) predict satisfaction with life. Related findings (Büssing et al 2013) show that the perception of being distant from God negatively correlates with life satisfaction and dispositional optimism. It is understandable if we think that spiritual dryness is a marker of crisis (Büssing et al 2016) and as such can be considered a threat to a global assessment of own-life quality.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Likewise, experiential representations of God or "heart knowledge" (Zahl and Gibson 2012) predict satisfaction with life. Related findings (Büssing et al 2013) show that the perception of being distant from God negatively correlates with life satisfaction and dispositional optimism. It is understandable if we think that spiritual dryness is a marker of crisis (Büssing et al 2016) and as such can be considered a threat to a global assessment of own-life quality.…”
Section: Discussionmentioning
confidence: 82%
“…The majority of studies report that religious struggles worsen health (Ano and Vasconcelles 2005;Smith et al 2003), weaken personal adjustment and harm well-being (Ano and Vasconcelles 2005), make recovery and rehabilitation more difficult (Fitchett et al 1999), and predict higher mortality rates (Pargament et al 2001). In a cross-sectional survey, Büssing and colleagues (Büssing et al 2013) found that a lack of positive spiritual feelings ("spiritual dryness") among 3.824 Catholic priests correlated moderately negatively with life satisfaction. Correspondingly, results derived from an ongoing nationwide survey in the United States among participants at least 66 years old (Krause 2015) showed that greater religious doubt was associated with less life satisfaction.…”
Section: Life Satisfaction and R/s Strugglesmentioning
confidence: 99%
“…To operationalize feelings of "spiritual dryness," we used the 6-item Spiritual Dryness Scale (SDS) which had a good internal consistency (Cronbach's α = 0.87) [1]. The instrument addresses whether or not individuals have experienced such phases of "spiritual dryness," feelings that God is distant, that one's prayers go unanswered, of being "spiritually empty" or of not being able to give any more (both in terms of a spiritual exhaustion), and finally of being abandoned by God.…”
Section: Spiritual Dryness Scalementioning
confidence: 99%
“…Such feelings of "spiritual dryness" were operationalized as various perceptions and emotional states, i.e., as a perception to be distant from God, regardless of one's efforts to draw close to Him, that one's prayers go unanswered, the perception of being spiritually empty or of not being able to give any more (both in terms of spiritual exhaustion), and even feelings of being abandoned by God [1,2]. Thus, these feelings are not primarily a matter of depression (although it might be related), but an inability to get in contact with God and to communicate with Him (i.e., in prayer) and thus to perceive God in one's life concerns.…”
Section: Introductionmentioning
confidence: 99%
“…A short version of the PSS (Büssing, Günther, Baumann, Frick, & Jacobs, 2013;Cohen & Williamson, 1988) was used for measuring perceived stress in the past month. The scale consists of 10 items coded from 0 = never to 4 = very often.…”
Section: Perceived Stress Scale (Pss)mentioning
confidence: 99%